Client’s Perspective: Realization as a New Generation Process for Software Project Development and Management - Akbar, R.; Hassan, M.F.; Safdar, S.; Qureshi, M.A. (2010)
IT industry despite the wide use of most modern tools and technologies has been unable to achieve targeted success. Awry situations in projects have become routine matter. Besides technical other factors influencing software development activities also need to be considered. Software development and consultancy organizations must realize the importance of such technical and non-technical factors like client’s perspective, organizational environment, company policies and social infrastructure. Identification and managing such issues are more cumbersome than routine practical tasks. This paper focuses on one of the most important and critical cum technical factor client’s perspective. Elements comprising client’s perspective are identified and the spider web model is proposed to practice it. Real projects based evaluation is made. The results elaborate the client based practices. Client based practices would be an advent of new generation of processes to overcome IT industry dilemma.